O português como língua nacional angolana: uma análise a partir da investigação do uso das formas pronominais nós e a gente - Kialanda, Kialunda Sozinho (2023)
In this work, we discuss the need to consider the Portuguese language beyond the official language and discuss it as a part of the linguistic and cultural identity of Angolans alongside other languages ​​considered national. We deal here with attention with the Portuguese of Angola, understood as a legitimate variety, however marginalized, in the instances and in the registers that make the language official, conferring prestige to the normative standard. This is a study based on the theoretical-methodological assumptions of Variationist Sociolinguistics, with the main objective of discussing the sociolinguistic identity of Portuguese in Angola, based on the pronominal use in Portuguese spoken in Luanda. The perspective of analysis adopts a qualitative and quantitative approach in research and, in procedural terms, the data of the analysis were raised in a corpora sample of the Portuguese spoken in Luanda, extracted in the scope of the research project, In search of the roots of Brazilian Portuguese, which is in its third phase. From the analyses, with regard to the pronominal framework, the initial intention was to investigate the inflection of the pronominal case, but it was identified, mainly, the alternation of use with regard to the use of the forms "us" and "we", reason why this was the linguistic phenomenon chosen for this research. In this way, the results show that, regarding the use of “nós” and “a gente”, Angola presents a peculiar behavior, presenting quantitative differences in relation to Brazilian Portuguese and European Portuguese, but presents similarities to the Brazilian variety in relation to other languages. phenomena of the pronominal frame. We therefore understand these data as peculiar features of the Angolan norm, which has distanced itself from the European standard norm that is still taught in schools in that country.